SIRONA: Sustainable Integration of Regenerative Outer-space Nature and Agriculture. Part 2 — Design Development and Projected Performance. (July 2022) - Hava, Heather; Zhou, H. Larissa; Mehlenbeck, Chad; King, Abby; Lombardi, Elizabeth M.; Baker, Kyri; Kaufman, Andy; Correll, Nikolaus
Abstract: A comprehensive Bioregenerative Life Support System (BLiSS) for human Long-duration Space Exploration Missions (LDSEMs) requires an innovative design philosophy and novel technical solutions. SIRONA: Sustainable Integration of Regenerative Outer-space Nature and Agriculture is a greenhouse design that produces a wide variety of food sources and provides life support functions, including access to nature to improve astronaut restoration, relaxation, and recreation. In a previous paper (Hava et al., 2019), risk analyses, technologies, and system architecture were outlined, while this paper describes the foundational Living Systems Centered Design (LSCD) principles that informed the development of the greenhouse. Analyses on projected performance are also carried out to validate design assumptions and constraints. Highlights: Living Systems Centered Design was used to develop the SIRONA greenhouse to ensure the key considerations of health and well-being of the living systems, which includes humans being fully supported by the technologies and design of this SIRONA greenhouse. Recreation, food preparation areas and automation technologies are built into the food production greenhouse to improve crew health, well-being, human factors and workload. Genetic diversity and integrated technologies are used synergistically to manage the risks of crop and system hardware failures. The SIRONA greenhouse design received the Most Innovative Design Award in the 2019 NASA BIG Idea Competition and the SIRONA Part-1 paper received the AIAA 2019/2020 Space Architecture Committee Best Student Paper Award.